Art, science/technology and history museums on the web. (2nd September 2008) - Fotakis, Thomas; Economides, Anastasios A.
A framework for evaluating museums' websites is presented. This framework is applied to evaluate 210 museums' websites (70 art, 70 science/technology, and 70 history museums) worldwide. The evaluation results show that all three museums' categories present websites that stay at a satisfying, yet not exceptional, level. Science museums' sites lead the list, with art museums' sites following closely and history museums' sites coming in next. Almost all sites outperformed with respect to technical characteristics. However, many sites present inefficiencies regarding Interactivity and Feedback. Finally, suggestions for improvements are made.